2022
DOI: 10.1097/md.0000000000028692
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body reaction mimicking local recurrence from polyactide adhesion barrier film after laparoscopic colorectal cancer surgery

Abstract: Polyactide (PLA) barrier is one of the most commonly used materials to prevent the formation of postoperative adhesion. Even though previous studies supported the anti-adhesion efficacy of PLA barrier, there have been limited reports focusing on the associated foreign body reaction. We sought to investigate the potential complication of PLA barrier placement that could lead to unnecessary intervention. This is a retrospective study of colorectal cancer patients with laparoscopic surgery. Cases with stage IV un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Previously, we showed enhanced radiolabeled glucose (fluorodeoxyglucose; FDG) uptake in the PLA microenvironment, which was abrogated by inhibiting glycolysis . In agreement, persistent foreign body (sterile inflammatory) reactions to PLA devices employed after human surgeries manifest elevated FDG uptake, which could be mistaken for cancer recurrence. , By comparing glycolytic inhibition to neutralization strategies, we showed that the former was more effective in reducing CD86 (proinflammatory) expression in the amorphous PLA microenvironment, without affecting CD11b or F4/80 (macrophage recruitment) levels, supporting our in vitro model . Additionally, our bioenergetic model more robustly simulated sterile inflammatory protein expression, without the need to include IFN-γ or bacterial endotoxins in PLA in vitro studies.…”
Section: Discussionsupporting
confidence: 84%
“…Previously, we showed enhanced radiolabeled glucose (fluorodeoxyglucose; FDG) uptake in the PLA microenvironment, which was abrogated by inhibiting glycolysis . In agreement, persistent foreign body (sterile inflammatory) reactions to PLA devices employed after human surgeries manifest elevated FDG uptake, which could be mistaken for cancer recurrence. , By comparing glycolytic inhibition to neutralization strategies, we showed that the former was more effective in reducing CD86 (proinflammatory) expression in the amorphous PLA microenvironment, without affecting CD11b or F4/80 (macrophage recruitment) levels, supporting our in vitro model . Additionally, our bioenergetic model more robustly simulated sterile inflammatory protein expression, without the need to include IFN-γ or bacterial endotoxins in PLA in vitro studies.…”
Section: Discussionsupporting
confidence: 84%
“…We showed enhanced radiolabeled glucose (fluorodeoxyglucose; FDG) uptake in the PLA microenvironment which was abrogated by inhibiting glycolysis 6 . In agreement, persistent foreign body (sterile inflammatory) reactions to PLA devices employed after human surgeries manifest elevated FDG uptake, which could be mistaken for cancer recurrence 43,44 . By comparing glycolytic inhibition to neutralization strategies, we showed that the former was more effective in reducing CD86 (proinflammatory) expression in the amorphous PLA microenvironment, without affecting CD11b or F4/80 (macrophage recruitment) levels, supporting our in-vitro model 6 .…”
Section: Discussionmentioning
confidence: 84%
“…We observed increased glycolytic dependence in the PLA inflammatory microenvironment using sterile amorphous PLA, which was abrogated by 2DG, one of the glycolytic inhibitors applied in our in-vitro studies. Unsurprisingly, after surgical resection of colorectal and cervical tumors in human patients, chronic, sterile inflammation from PLA-based adhesion barriers elevate FDG uptake, falsely mimicking cancer recurrence 63,64 .…”
Section: Discussionmentioning
confidence: 99%